PENGEMBANGAN MEDIA VIDEO KETERAMPILAN DASAR MENGAJAR UNTUK MATA KULIAH PEMBELAJARAN MIKRO - Sugiharti, Gulmah; Dalimunthe, Makharany; Nasution, Mutiara Agustina; Sari, Dwy Puspita; Siregar, Muhammad Isa (Edukimia, 2024)
The Micro Teaching course aims to provide prospective teaching students with several basic teaching skills. The absence of micro laboratories and the difficulty of students in presenting basic teaching skills necessary for teachers or prospective teachers require learning media. Video media for basic teaching skills can overcome space and time limitations and be used repeatedly.  This research aims to determine the feasibility of the basic teaching skills video media being developed and to find out students' responses or interest in the basic teaching skills video media being developed. The type of this research is Research and Development (RD) with the ADDIE (Analyze, Design, Development, Implementation, and Evaluation). The results of the research show that the average validation scores for basic teaching skills video media design from material experts and media experts are 91% and 91.25%, so the basic teaching skills video media is declared very valid. Responses from 13 students also showed that the video media developed was very interesting with an average score of 85.81% in the very good category. Thus, video media for basic teaching skills is perfect for use in micro-learning lectures.